The Use Of Non-Standard Tasks In Teaching Physics In The System Of Continuing Education (Journal of Pedagogical Inventions and Practices, 2023)
This article is devoted to improving the application of non-standard tasks from the physics course in the formation of the professional training of future pedagogues in higher educational institutions of pedagogy, selecting and applying them to the educational process based on science programs and syllabuses, developing the level of knowledge of students, expanding their range of thinking, reflecting interdisciplinarity, science it is important to increase interest in and develop professional training. The methodical system of science is improved in students by reviewing the problems, tests and non-standard tasks related to the Department of Molecular Physics and Mechanics.